Fast delivery, on demand: how flexibility and individualization policy are enacted in Swedish municipal adult education - Diana Holmqvist; Per Andersson; Karolina Muhrman (Taylor & Francis Group, 2024)
ABSTRACTNational policy states that Swedish adult education should be flexible and individualized, based on students' needs. However, adult education in Sweden is a municipal responsibility with a high level of decentralization. Drawing on national policies, this study focuses on how the concepts of flexibility and individualization are enacted locally and what consequences this has for teaching and learning. Starting from a teacher perspective and based on qualitative interviews with 50 teachers, the article analyses how policy requirements for offering flexible and individualized adult education are being enacted, and what the consequences of this are for teaching and learning. The findings show how flexibility and individualization are put into practice through measures such as a fast study pace, continuous admission of students, and pressure on municipalities to maintain a broad course offer, often by turning to distance education. This enactment makes it easier for adult learners to fit education into their lives, but it also has consequences for the quality of teaching and learning. It is causing fragmentation, a learning environment where interactions mainly occur on an individual basis, an instrumental view of education, and teachers experiencing high workloads and low autonomy in making pedagogical decisions.